Medium-long-term results of carotid stenting in asymptomic stenosis of the carotid arteries - S. A. Bagin; Р. Е. Krainyukov; Z. Kh. Shugushev; D. A. Maksimkin; S. S. Saidov; S. V. Volkov; A. О. Korobkov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The article describes the experience of carotid stenting use in asymptomatic cerebral atherosclerosis. The study included 147 patients with unilateral asymptomatic carotid artery disease. The evaluation of mid-longterm results of carotid stenting in patients with asymptomatic stenosis was carried out in comparison with the use of conservative treatment in this category of patients (“optimal drug treatment”). In the course of the work, no significant intergroup difference was revealed in the incidence of adverse outcomes (TIA/stroke, death from stroke,) within a year from the moment of surgical treatment or the beginning of complex correction of risk factors.